Diseased, differentiated and difficult: Strategies for improved engineering of in vitro neurological systems - Elder, Nicholas; Fattahi, Faranak; McDevitt, Todd C.; Zholudeva, Lyandysha V. (Frontiers in Cellular Neuroscience, 2022)
The rapidly growing field of cellular engineering is enabling scientists to more effectively create in vitro models of disease and develop specific cell types that can be used to repair damaged tissue. In particular, the engineering of neurons and other components of the nervous system is at the forefront of this field. The methods used to engineer neural cells can be largely divided into systems that undergo directed differentiation through exogenous stimulation (i.e., via small molecules, arguably following developmental pathways) and those that undergo induced differentiation via protein overexpression (i.e., genetically induced and activated; arguably bypassing developmental pathways). Here, we highlight the differences between directed differentiation and induced differentiation strategies, how they can complement one another to generate specific cell phenotypes, and impacts of each strategy on downstream applications. Continued research in this nascent field will lead to the development of improved models of neurological circuits and novel treatments for those living with neurological injury and disease.